NAVIGATION RANGE AND DURATION OF FLIGHT OF UNMANNED AERIAL VEHICLE - Udartsev, Ievgen; Bondar, Alexandr; Plakhotniuk, Ievgen (Proceedings of National Aviation University (archive), 2014)
The problem of calculation of navigation range and the flight duration, different from estimated technicalrange by the accounting of operational features in balancing, influence of atmospheric flight conditions and the specificfeatures influencing aerodynamic resistance of unmanned aerial vehicle is considered.